Study of Fluoride Affinity by Zirconium Impregnated Walnut Shell Carbon in Aqueous Phase: Kinetic and Isotherm Evaluation - M. Rajan; G. Alagumuthu (Journal of Chemistry)
This paper examines the kinetics of fluoride removal from water by the adsorbent zirconium-impregnated walnut-shell carbon (ZIWSC), exploring the mechanisms involved. The dependence of the adsorption of fluoride on the pH of the solution has been studied to achieve the optimum pH value and a better understanding of the adsorption mechanism. The presence of bicarbonate ions in aqueous solution was found to affect the fluoride removal indicating that these anions compete with the sorption of fluoride on adsorbents. The kinetic profile has been modeled using pseudo-first-order model, pseudo-second-order model, and intraparticle diffusion model. The kinetic sorption profiles offered excellent fit with pseudo-second-order model. Adsorption isotherms have been modeled by Langmuir, Freundlich, and Temkin equations, and their constants were determined. The equilibrium adsorption data were fitted reasonably well for Freundlich isotherm model. XRD and SEM patterns of the ZIWSC were recorded to get better insight into the mechanism of adsorption process.